TBIO-18. LIQUID BIOPSY DETECTION OF GENOMIC ALTERATIONS IN PEDIATRIC BRAIN TUMORS FROM CELL FREE DNA IN PERIPHERAL BLOOD, CSF, AND URINE. Issue 2 (22nd June 2018) - Pages, Melanie; Rotem, Denisse; Gydush, Gregory; Reed, Sarah; Rhoades, Justin; Ha, Gavin; Lo, Chris; Tracy, Adam; Jones, Robert; Becker, Sarah; Haller, Michaela; Chi, Susan; et al.
Abstract: Brain tumors often require invasive neurosurgical procedures for diagnosis and tissue acquisition to guide precision medicine. Detection of tumor-derived cell-free DNA (cfDNA) would facilitate tumor profiling without risk of surgery-related morbidity and provide a means of tumor surveillance. Our aim is to validate a sample collection procedure and develop highly sensitive and specific methodologies to detect tumor-derived cfDNA in CSF, plasma and urine from pediatric patients with brain tumors to identify clinically relevant genomic alterations. Since July 2016, we have collected blood, urine and CSF samples from 192 patients across all histological subtypes at Dana-Farber Cancer Institute/Boston Children's Hospital. In parallel, we sequenced the tumors to identify tumor-specific genomic alterations. We optimized a method to process cfDNA and perform ultra-low pass whole genome sequencing (ULP-WGS) using unique molecular identifiers, confirming we can reliably construct sequencing libraries from CSF-, plasma- and urine-derived cfDNA. ULP-WGS has also been used to assess sequencing library quality, copy number variations (CNVs) and tumor fraction. The vast majority of samples undergoing ULP-WGS exhibited no CNVs, consistent with either absence in the tumor or low levels of tumor-derived cfDNA. To distinguish between these, we developed a hybrid capture sequencing panel covering 46 genes, allowing identification of specific mutations and fusions more common in pediatric brain tumors. We are currently assessing the specificity and sensitivity of our assays for detection of tumor-derived cfDNA. Our results will provide insights regarding the feasibility of cfDNA assays to guide clinical care in children with brain tumors.